Work-Family Interface, Workplace Well-Being and Psychological Detachment on Work from Home System - Michael, Michael; Zamralita, Zamralita (TAZKIYA Journal of Psychology, 2024)
The COVID-19 pandemic has impacted employees in numerous ways, notably through the shift to work-from-home (WFH) arrangements. This transition has disrupted employees’ workplace well-being (WWB), with blurred boundaries between family and work life becoming more common. The challenge of balancing work and family demands under WFH conditions is referred to as the work-family interface (WFI). This study explores the effect of WFI on WWB and examines whether psychological detachment—defined as a recovery experience that allows individuals to mentally disengage from work to restore personal resources—moderates this relationship. The implementation of WFH during COVID-19 pandemic has posed a challenge of balancing the interaction between work and family or can be known as work-family interface (WFI). Psychological detachment as a form of recovery experience to replenish an individual's resource is assumed to moderate the relationship between WFI and WWB. So this study aims to look at the impact from WFI to WWB and also the moderation effect of psychological detachment. The study was conducted on 143 employees using convenience sampling, a non-probability sampling method. The instruments utilized in this study are the Work Family Interface from the Work-Family Interface Scale, with a reliability score of α = .728; the Workplace Well-being from the Workplace Well-being Questionnaire, with a reliability score of α = .893; and the Psychological Detachment from the Recovery Experience Questionnaire, with a reliability score of α = .825 and ω = .828. The results demonstrated that the Work-Family Interface (WFI) exerts a significant influence on workplace well-being (WWB) (p = .000). Furthermore, the findings substantiated that the four dimensions of the WFI markedly impact WWB (p = .000). However, the hypothesis that psychological detachment acts as a moderator in the relationship between WFI and WWB was not supported (p = .263, p > .05).